Identifikasi Karakteristik Morfologi dan Sifat Fisik Tanah Akibat Konversi Penggunaan Lahan Berbeda di Negeri Hatu, Kecamatan Leihitu Barat - Robby G Risamasu; Irenne Marlissa (Fakultas Pertanian, Universitas Pattimura, 2020)
Field research and laboratory analysis results were obtained on the parameters that experienced a changein the morphology and physical properties of soil including the soil color at each site. It had beenobserved that the color looked brown due to the organic materials associated with Fe, yellow due to ironoxide compounds such as hydroxide Fe2O3.H2O (hydroxide iron) and red was caused by soil parentmaterial. We examined state structure and consistency. The soil structure of the three lands use was arounded cube and consistency ranged from slightly sticky to sticky, wet. Soil water content at each studysite varied according to land use and density of land cover (canopy). The values generated by a heavyvolume of soil in each land use were different. The values produced different soil porosity. This wasrelated to several soil properties, including the type and number of plants, roots, and organic mattercontent.